2005
DOI: 10.1124/jpet.105.085126
|View full text |Cite
|
Sign up to set email alerts
|

YC-1 [3-(5′-Hydroxymethyl-2′-furyl)-1-benzyl Indazole] Inhibits Endothelial Cell Functions Induced by Angiogenic Factors in Vitro and Angiogenesis in Vivo Models

Abstract: Angiogenesis is a process that involves endothelial cell proliferation, migration, invasion, and tube formation, and inhibition of these processes has implications for angiogenesis-mediated disorders. The purpose of this study was to evaluate the antiangiogenic efficacy of YC-1 [3-(5Ј-hydroxymethyl-2Ј-furyl)-1-benzyl indazole] in well characterized in vitro and in vivo systems. YC-1 inhibited the ability of vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) in a dose-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 32 publications
3
26
1
Order By: Relevance
“…Furthermore, YC-1 was observed to suppress NF-κB activity via inhibition of the phosphorylation and degradation of I-κBα and to induce apoptosis in prostate cancer PC-3 cells (17). Moreover, YC-1 was recognized to inhibit angiogenesis via repression of VEGF by downregulating HIF-1 resulting in reducing cancer cell proliferation (16,(29)(30)(31). In the present study, our results showed that YC-1 repressed the protein level of HER2.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Furthermore, YC-1 was observed to suppress NF-κB activity via inhibition of the phosphorylation and degradation of I-κBα and to induce apoptosis in prostate cancer PC-3 cells (17). Moreover, YC-1 was recognized to inhibit angiogenesis via repression of VEGF by downregulating HIF-1 resulting in reducing cancer cell proliferation (16,(29)(30)(31). In the present study, our results showed that YC-1 repressed the protein level of HER2.…”
Section: Discussionsupporting
confidence: 58%
“…In vivo xenograft studies have also revealed that YC-1 exhibits marked antitumor activity against various cancer cell lines and prolongs the survival time of tumor-bearing mice, but without evident toxic effects (16,17). The anticancer effect of YC-1 appears to be a consequence of its multiple actions, including anti-inflammation activity, suppression of the hypoxia-inducible factor-1α (HIF-1α) expression, influence on the differentiation of stem cells, and promotion of NK cell differentiation by activating the p38-MAPK pathway (18)(19)(20).…”
Section: Clc604 Preferentially Inhibits the Growth Of Her2-overexpresmentioning
confidence: 99%
“…Immunoprecipitation and Western Blot Analysis Nuclear and mitochondrial fractionation were done as described previously (19). Total protein was determined and equal amounts of protein were separated by 10-15% SDS-PAGE and immunoblotted with specific primary antibodies.…”
Section: Apoptosis Detectionmentioning
confidence: 99%
“…More recently, YC-1 was reported to decrease hypoxia-induced HIF-1a accumulation and expression of downstream HIF-1 target genes, including those for vascular endothelial growth factor (VEGF) and erythropoietin, in vitro (Chun et al, 2001) and to inhibit angiogenesis and tumor growth in animals (Yeo et al, 2003;Pan et al, 2005). Although YC-1 has become a valuable research tool for studies of HIF-1a (Moeller et al, 2004;Funasaka et al, 2005), the mechanism by which YC-1 exerts its antitumor effects has not been established.…”
Section: Introductionmentioning
confidence: 99%